2005
DOI: 10.1093/mutage/gei062
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of the utility of the yeast GreenScreen assay in pharmaceutical screening

Abstract: In this paper we describe an initial reproducibility study of 12 proprietary compounds followed by the assessment of 51 marketed pharmaceuticals and, lastly, a summary of the data so far from 2698 proprietary compounds from the Johnson & Johnson (J&J) compound library, in the yeast GreenScreen assay (GSA). In this assay, a reporter system in the yeast cells employs the DNA damage inducible promoter of the RAD54 gene, fused to the extremely stable green fluorescent protein (GFP). The assay proved to be very rob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(28 citation statements)
references
References 14 publications
0
28
0
Order By: Relevance
“…The UDS test can also be applied in vivo. A yeast-based fluorescence reporter assay for genotoxicity, termed GreenScreen, was introduced especially for application in high-throughput test systems [96]. The endpoint of the test represents chromosomeand DNA-metabolizing enzymes of yeast, as indicated by GFP-labeled expression reporter.…”
Section: Genotoxicitymentioning
confidence: 99%
“…The UDS test can also be applied in vivo. A yeast-based fluorescence reporter assay for genotoxicity, termed GreenScreen, was introduced especially for application in high-throughput test systems [96]. The endpoint of the test represents chromosomeand DNA-metabolizing enzymes of yeast, as indicated by GFP-labeled expression reporter.…”
Section: Genotoxicitymentioning
confidence: 99%
“…This assay may be developed into a rather high-throughput test: one study reported screening 2698 compounds in a little more than a year [40]. An interlaboratory "ring trial" with 19 coded compounds concluded that the method provides an effective reproducible and reliable higher throughput screening alternative to the standard Ames test [41].…”
Section: The Ames Test Variantsmentioning
confidence: 99%
“…The promoter sequences of RAD51, RAD54, HUG1, RNR2, and RNR3 have been used in reporter plasmids to detect agents that damage DNA, and assay strains have been shown to respond to various genotoxic agents such as gamma ray, methyl methanesulfonate, 4-nitroquinoline-1-oxide, methyl-Nnitro-N-nitrosoguanidine, cisplatin, and camptothecin (Walmsley et al, 1997;Billinton et al, 1998;Afanassiev et al, 2000;Boronat and Piña, 2006;Benton et al, 2007;Liu et al, 2008;Wei et al, 2013). The RAD54-GFP reporter assay strain has been validated as a genotoxicity test called the GreenScreen Assay (Cahill et al, 2004;Walsh et al, 2005;Van Gompel et al, 2005;Knight et al, 2007). The promoter sequences of the CUP1, SEO1, and UFO1 genes have been used to detect heavy metals.…”
Section: Introductionmentioning
confidence: 99%